A CONSTRUCTION OF FOUR-TIER TEST TO IDENTIFY THE MISCONCEPTIONS’ LEVEL AND SOURCE ON MATERIAL OF HEAT - Ahmad Ahsin Akmali (Jurnal Kependidikan, 2018)
This study was aimed at generating the instruments that are focused on being able to diagnose the level and causes of misconceptions. The method used in this study was the Development Validation research method. The subjects participated in implementation activities were 243 XI grade of high school students in Cimahi. At the instrumental study, the diagnostic level and causes of misconceptions were constructed in Four-Tier Test format using questionnaire integration. Four-Tier Test with the integration of questionnaires generated through this study was a feasible test tool with a CVR score of 0.837, product moment correlation score of 0.733 and the percentage of conformity reaching 88.89%. The results of the instrument implementation shows that students experience misconceptions were quantitatively very low level of misconceptions but qualitatively high. The highest level of misconception reached 25.10% of the total sample. The cause of the most misconceptions in heat material is because the results of personal thinking reached 62.70%. The results of this study show the background to misconception is reading texts from the internet and fiction stories from comics or magazines.KONSTRUKSI FOUR-TIER TEST UNTUK MENGIDENTIFIKASI LEVEL DAN PENYEBAB MISKONSEPSI PADA MATERI KALORAbstrakPenelitian ini bertujuan untuk menghasilkan instrumen yang difokuskan untuk mampu mendiagnosis level sekaligus penyebab miskonsepsi. Metode yang digunakan dalam penelitian ini adalah metode penelitian Development Validation. Subjek pada kegiatan implementasi adalah 243 siswa sekolah menengah atas kelas XI yang ada di Kota Cimahi. Pada penelitian instrumen, diagnostik level dan penyebab miskonsepsi dikonstruk dalam format Four-Tier Test dengan integrasi angket. Four-Tier Test dengan integrasi angket yang dihasilkan melalui penelitian ini merupakan alat tes yang layak dengan skor CVR 0,837 dan skor korelasi product moment 0,733 serta persentase kesesuaian mencapai 88,89%. Hasil implementasi instrumen menunjukkan bahwa peserta didik mengalami miskonsepsi dengan level miskonsepsi sangat rendah secara kuantitatif namun tinggi secara kualitatif. Level miskonsepsi paling tinggimencapai 25,10% dari total sampel. Penyebab miskonsepsi terbanyak pada materi kalor adalah karena hasil pemikiran pribadi yang mencapai 62,70%. Hasil penelitian ini mengemukakan bahwa latar belakang miskonsepsi adalahteks bacaan dari internet dan cerita fiksi dari komik atau majalah.